Sources in election news frame: transition, selection and authority - Mat Saad, Mohd Zuwairi; Mustaffa, Normah; Ahmad, Abdul Latiff; Abu Hassan, Badrul Redzuan (Universiti Kebangsaan Malaysia, 2016)
Sources play a key role in reporting news. This is because, according to Conrad (1999) journalist depends on the source in their news when delivering information to the audience. There are various categories of sources in the news. Categories of sources include government officials, industry officials, elites, scientists, doctors, lawyers and etc. In political news, various sources range from active politicians to ordinary citizens who engage actively in politic. Dimitrova and Strömbäck (2012) said political source category specific to source more closely linked to individuals who are active in political activity, including ordinary citizens. This article discusses the main popular sources used in news reporting of by-election in 1987, 1997 and 2014 in Utusan Malaysia and Berita Harian using the content analysis method. Content analysis study was conducted on 419 election news articles that were randomly selected. A phenomenology of sources were later reinforced through in-depth interviews to journalists to see the selection and source of authority. The study found that politicians in the country are the main sources of election news reporting. Otherwise, source selection is made by journalists to report any issues or events on election. The sources should have authority over a field in giving opinions or answers everything concerns about political issues